EVALUASI DISTRIBUSI DAN PENYIMPANAN VAKSIN DI DINAS KESEHATAN KABUPATEN MAJENE SULAWESI BARAT - , Ummu Kalsum T ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Backgrounds : Immunization program has been proved effective and possesses the most significant effect in the program of community health improvement. The worst coverage of of basic immunizations in Indonesia by the year 2010 was West Sulawesi 32,1 %. One reason of this inadequate coverage was impaired and expired vaccines in public health centers that make them unable for usage. Research then should be conducted regarding the distribution and storage of vaccine in Health Office and public health centers of Majene district. Aim : The research generally aimed at determining the distribution and storage of vaccines in Health Office of Majene district. Methods: The research employed a case study descriptive design using retrospective qualitative and quantitative data. Data were colllected by in- depth interview, questionnaire, and observation. Results : The policy of immunization program in Majene district was still limited to discussions only without any real issuing of legal regulations. The human resources was inadequate. The budget available for the operation of immunization program was still lacking. Management Information System of noting and manual reporting was not yet optimal. Facilities and supporting facilities were not yet adequate and supervision was not yet effective. Distribution of vaccine in Majene district was not yet optimal since there were differences between the knowledge of officers in public health centers regarding the correct way to carry vaccine and no standard operational procedure of vaccine distribution available. Vaccine storage in all public health centers had not yet achieved standard and Ulumanda public health center had the worse condition of vaccine storage between all public health centers. Effectivity of immunization program in Majene was adequate regarding the coverage of basic immunizations except for Ulumanda public health centers. When viewed from the target of achievement of UCI 2010, only Pamboang and Malunda public health centers that were able to meet the target stated by Indonesiaâs Department of Health. Conclusion : Vaccine distribution and storage was not yet optimal since they hadnât meet the standard stated by Indonesiaâs Department of Health regarding the guidelines for conducting immunization.